2008
DOI: 10.1063/1.2976312
|View full text |Cite
|
Sign up to set email alerts
|

Thermochemical control of oil droplet motion on a solid substrate

Abstract: Through the thermochemical control of a liquid droplet on a solid substrate, we investigated the motion of the droplet and the underlying mechanism. Depending on the contact angle of the running droplet on the substrate with a chemical gradient coating, we observed two different behaviors for the droplet under local laser heating: reversing for a contact angle larger than a critical value (∼90°) and passing for a smaller value. The motion at the laser heating position was found to be closely related to the con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…Tseng et al 31 found that the droplet shape would change during motion. Recently, Song et al 30 indicated that capillary flow plays an important role in the thermocapillary migration of a droplet. Unfortunately, experimental works have only been conducted for droplet movement on a specific solid surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tseng et al 31 found that the droplet shape would change during motion. Recently, Song et al 30 indicated that capillary flow plays an important role in the thermocapillary migration of a droplet. Unfortunately, experimental works have only been conducted for droplet movement on a specific solid surface.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28][29][30][31][32][33] The main objective of the theoretical studies has been to predict the steady migration velocity of the droplet. Lubrication approximation has been employed for this purpose in several works.…”
Section: Introductionmentioning
confidence: 99%
“…Smith 8 showed that the thermocapillary cell inside the droplet distorts the free surface and changes the dynamic contact angles. Song et al 11 employed a chemical gradient coating and local laser heating to manipulate the migration of a droplet. They pointed out that the direction of motion is closely related to the change in the contact angle.…”
Section: Introductionmentioning
confidence: 99%
“…This technique has been applied to change in size of droplets by voltage. [21][22][23][24] The voltage-dependency of the size means that the curvature radius of the sessile drop can be controlled with the voltage. Then the drop may work as a focal length-adjustable lens.…”
mentioning
confidence: 99%